Strategies for hera equipment LLC's development of rental equipment business in the Mongolian mining industry - Aung Khin, Mi Mi (2014)
Mongolia is an emerging country that has immense opportunities. 82 of the total 111 elements of the Periodic Table can be found in commercially exploitable volumes in Mongolia. The future of Mongolia is undoubtedly defined by its mining industry, much like how it has also been defined by its great hero, Chinggis Khan. There is no lack of news coverage, analysis and business journals covering the major multinational corporations and foreign investments going into Mongolia. However, very little is known about the local enterprises in Mongolia and how they are leveraging on the immense business opportunities from the mining industry. Through extensive study of a local Mongolian mining equipment supplier, we look into its perspective and uncover the unique opportunities and challenges in the market. We also provided strategies and recommendations using the Balanced Score Card (BSC) framework.